2012
DOI: 10.1016/j.cmet.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Pten Positively Regulates Brown Adipose Function, Energy Expenditure, and Longevity

Abstract: Aging in worms and flies is regulated by the PI3K/Akt/Foxo pathway. Here we extend this paradigm to mammals. Pten(tg) mice carrying additional genomic copies of Pten are protected from cancer and present a significant extension of life span that is independent of their lower cancer incidence. Interestingly, Pten(tg) mice have an increased energy expenditure and protection from metabolic pathologies. The brown adipose tissue (BAT) of Pten(tg) mice is hyperactive and presents high levels of the uncoupling protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
279
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(305 citation statements)
references
References 69 publications
22
279
2
2
Order By: Relevance
“…Phosphatase and tensin homolog (PTEN) has also been reported to be a functional target gene of miR-382 (42); PTEN increases brown adipose function and energy expenditure (43). We observed increases in PTEN protein levels in the adipose tissue of BLC-supplemented mice (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…Phosphatase and tensin homolog (PTEN) has also been reported to be a functional target gene of miR-382 (42); PTEN increases brown adipose function and energy expenditure (43). We observed increases in PTEN protein levels in the adipose tissue of BLC-supplemented mice (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…In addition to our study, PTEN overexpression in transgenic mice was recently shown to induce increased energy expenditure, hyperactive brown adipose tissues and reduced body fat accumulation [11,12]. It is therefore clear that chronic alterations of PTEN signalling in peripheral organs are correlated with adipose tissue plasticity.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, PTEN heterozygosity and PTEN tissue-specific deletions in muscle or adipose tissue all lead to improved glucose tolerance in healthy or obese/diabetic mice [8][9][10]. However, adding to the complexity of PTEN function, transgenic mice, overexpressing PTEN, display increased energy expenditure and insulin sensitivity [11,12]. Regarding the liver, we previously reported that PTEN is downregulated in steatotic livers of obese patients, as well as in rat models of genetic or diet-induced obesity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, lipid droplet content was lower (Fig. 3H-J), pointing to higher intracellular lipolysis (18).…”
Section: Salsalate Reverses Hfd-induced Obesity and Improves Glucose mentioning
confidence: 99%